Analysis of Government Budget in Islamic View: Case of Aceh Government Budget - Putri Bintusy Syathi; Abdul Ghafar Ismail (Share: Jurnal Ekonomi dan Keuangan Islam, 2015)
Aceh province has a special right to implement Sharia principles throughout the area (Law Number 11/2006) though Indonesia is not an Islam country. Among the Sharia laws implementation, government budget was one of the first to be carried out in the province. It was showed up as Zakat post in the APBD (local government budget). The issue is whether putting in the Zakat post was enough to demonstrate an Islamic based budget as well as the transparence of zakat disbursement. Therefore, this paper trying to analyze the existing budget based on Sharia principles (Islamic Law) as explained by Chaudhry (1999) and Kahf (1997) The provincial budget needs improvement to be more sharia compliance. Fulfilling the Sharia criterion consequently will improve the accountability, transparency and the fairness of the budget toward people needs and development enhancing. ABSTRAK - Aceh adalah provinsi yang memiliki hak khusus dalam mengimplementasikan prinsip- prinsip syariah dalam wilayahnya (Undang- Undang no.11 tahun 2006) walaupun Indonesia bukanlah suatu negara Islam. Diantara implementasi hukum syariah, anggaran pemerintah adalah satu hal yang pertama yang dikelola dalam provinsi ini. Hal ini muncul pada pos zakat pada APBD (Anggaranan Pengeluaran dan Belanja Daerah). Masalahnya adalah apakah penempatan dana Zakat sudah cukup untuk menunjukkan sebagai anggaran yang berbasis Islam serta transparansi dalam penyaluran zakat. Untuk itu paper ini bertujuan untuk menganalisis anggara yang ada berdasarkan prinsip- prinsip syariah (Hukum Islam) seperti yang telah dijelaskan oleh Chaudury (1999) dan Kahf (1997). Anggaran provinsi perlu perbaikan agar lebih patuh syariah. Dengan terpenuhinya kriteria syariah maka akan meningkatkan akuntabilitas, transparansi, dan keadilan dalam anggaran terhadap kebutuhan masyarakat dan meningkatkan pembangunan.